Better schools for Europe - Erich Gundlach; Ludger Wößmann (EIB Papers, 2001)
We try to identify which economic factors might be responsible for the large international differences in student performance. We present time series evidence for a number of European countries which suggests that rising educational expenditures obviously did not improve student performance. This finding is largely in line with the international literature on the (in)effectiveness of schooling expenditures and implies that schooling is often provided inefficiently in Europe. Therefore, we speculate that a reform of the institutions which govern the incentives within European schooling systems may be needed to achieve improved student performance.
Keywords: 330; Schule; Produktivität; Bildungsniveau; Schulfinanzierung; Bildungsinvestition; Bildungsreform; Institutioneller Wandel; Ökonomischer Anreiz; EU-Staaten; USA